2022
DOI: 10.1021/acsami.2c04482
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer MSi2P4 (M = V, Nb, and Ta) as Highly Efficient Sulfur Host Materials for Lithium–Sulfur Batteries

Abstract: Despite the high capacity and low cost of lithium–sulfur (Li–S) batteries, their commercialization is greatly blocked by multiple bottlenecks including the shuttle effect of lithium polysulfides (LiPSs), poor conductivity of sulfur, and sluggish reaction kinetics. Herein, we propose novel two-dimensional MSi2P4 (M = V, Nb, and Ta) monolayers as promising sulfur hosts to improve the Li–S battery performance. Our calculations show that MSi2P4 monolayers offer moderate binding strengths to the polysulfides, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…[44] Beyond MoSi 2 N 4 and WSi 2 N 4 monolayers, the family of MA 2 Z 4 monolayers [32] also exhibit enormously rich physical and chemical behaviors, including nontrivial topological phases, [32] valley-contrasting physics, [45][46][47][48] nonlinear optical response, [49] hydrogen (oxygen) evolution catalytic performance, [50,51] and superior electrocatalytic activity for energy storage application. [52] Driven by the success of vdWH material engineering, MoSi 2 N 4 -based vdWHs have also been intensively studied recently. For example, MoSi 2 N 4 interfaced with InSe, [53] blue phosphorus, [54] C 2 N, [55] CrCl 3 , [56] C 3 N 4 , [57] MoS 2 , [58] graphene, [59] NbS 2 , [59] GaN, [60] ZnO, [60] MoSe 2 , [61] Cs 3 Bi 2 I 9 , [62] MoGe 2 N 4 , [63] MoGeSiN 4 , [64] and MoSH [65] have been computationally predicted to exhibit efficient photocatalytic water splitting, [53][54][55] strain-tunable valley splitting effect, [56] strong optical absorption in the visible light regime with strain, and field-effect tunable band structures.…”
Section: D Materials Van Dermentioning
confidence: 99%
“…[44] Beyond MoSi 2 N 4 and WSi 2 N 4 monolayers, the family of MA 2 Z 4 monolayers [32] also exhibit enormously rich physical and chemical behaviors, including nontrivial topological phases, [32] valley-contrasting physics, [45][46][47][48] nonlinear optical response, [49] hydrogen (oxygen) evolution catalytic performance, [50,51] and superior electrocatalytic activity for energy storage application. [52] Driven by the success of vdWH material engineering, MoSi 2 N 4 -based vdWHs have also been intensively studied recently. For example, MoSi 2 N 4 interfaced with InSe, [53] blue phosphorus, [54] C 2 N, [55] CrCl 3 , [56] C 3 N 4 , [57] MoS 2 , [58] graphene, [59] NbS 2 , [59] GaN, [60] ZnO, [60] MoSe 2 , [61] Cs 3 Bi 2 I 9 , [62] MoGe 2 N 4 , [63] MoGeSiN 4 , [64] and MoSH [65] have been computationally predicted to exhibit efficient photocatalytic water splitting, [53][54][55] strain-tunable valley splitting effect, [56] strong optical absorption in the visible light regime with strain, and field-effect tunable band structures.…”
Section: D Materials Van Dermentioning
confidence: 99%
“…Our calculations show that the adsorption energies of soluble Li 2 S n on TM@In 2 Se 3 range from −3.64 to −2.23 eV, which are significantly lower than the range of adsorption energies calculated on electrolyte molecules (DOL and DME), which vary from 0 to 1.00 eV. 50–52 This means that the TM@In 2 Se 3 is capable of immobilizing the Li 2 S n species and effectively suppress the LiPSs dissolution. In this sense, the strong adsorption strength for Li 2 S n species adsorbed on TM@In 2 Se 3 indicates that engineering In 2 Se 3 via 3d TM atom adsorption can suppress the shuttle effect.…”
Section: Resultsmentioning
confidence: 65%
“…Owing to their exceptional electronic conductivity and distinctive electronic structure, transition metal sulfides (TMSs) can be used to effectively trap LiPS clusters and prevent them from shuttling. , Recently, vanadium disulfide (VS 2 ) has gained much attention as an anchoring material for LiPSs due to its excellent conductivity and surface activity. After a comparative study of the anchoring effects of VO 2 and VS 2 nano-sheets, Wang et al concluded that VS 2 contains more favorable properties in hosting the sulfur cathode in Li–S batteries . In a similar study, Chen et al proposed an analogous periodic law for first-row TMSs and claimed that VS has the strongest anchoring on LiPSs with a relatively low lithium-ion diffusion barrier .…”
Section: Introductionmentioning
confidence: 99%